the correct answer is option c
in this question first we use the sum and difference formula :
cos (a-b) = cos(a) cos(b) + sin (a) sin (b)
let a = 180 and b = q, then
cos (180-q) = cos (180) cos (q) + sin (180) sin (q)
now the sin of 180 degree is 0. since 0 multiplying with anything leaves 0, this makes sin (180) sin (q) = 0
cos (180-q) = cos (180) cos(q)
now the cos of 180 degree is -1.
cos(180-q) = -1 cos(q), or cos (180-q) = -cos(q)
dawn is selling her mp3 player for 30$.
40 x 0.75 = 30
hope this : )